Variability of winter cooling affects intensity of phytoplankton spring blooms – how resilient is the ciliate assemblage composition to changes in food availability? - Schalch-Schuler, Martina; Wüest, Alfred; Dirren-Pitsch, Gianna; Niedermann, Rafael; Bassin, Barbara; Köster, Oliver; Pernthaler, Jakob; Posch, Thomas (Frontiers in Protistology, 2024)
After years of partial winter mixing in Lake Zurich (Switzerland), a complete turnover of the water column reoccurred during winter / spring 2021. It was favored by a cold, windy winter and a small difference of water temperatures between the surface zone and a hypolimnion (deep water zone) that had gradually warmed during the previous years. The trend of declining phytoplankton spring blooms due to incomplete winter mixing was interrupted by mass development of algae due to the upwelling of nutrients accumulated in the hypolimnion. The effects of this singular deep mixing on the microbial food web during spring were studied in a high-frequency sampling campaign and compared with data from two years of partial winter mixing (2020 and 2022). A particular focus was put on the quantitative composition of the ciliate assemblage. Our results showed that not all organisms reacted equally to the nutrient (phosphorus) boost in the surface zone. Centric diatoms and cryptophytes profited most directly from the deep mixing, outcompeting the otherwise dominant cyanobacterium Planktothrix rubescens. Heterotrophic bacteria and their top predators, the 'heterotrophic nanoflagellates' trophic guild, were less affected by the nutrient supply and showed only short-lived increases of maximal biomass. The assemblage composition of ciliate morphotypes was highly resilient over the three years, presumably due to the range of acceptable food items of the predominant omnivorous species.However, numerous ciliate morphotypes showed brief mass development in 2021, and Balanion planctonicum, small Urotricha species and tintinnids were significantly more frequent than in 2020/2022. Small interception-feeding morphotypes apparently profited from the rich supply of their cryptomonad food, and tintinnid morphotypes additionally benefited from the availability of building material (e.g., centric diatom shells) for their loricae. In summary, we show that effects of lake warming in deep stratifying lakes are not as unidirectional as previously presumed, and we reveal resilience of the pelagic ciliate morphotype assemblage to lake warming related interannual variability in Lake Zurich.